2012
DOI: 10.1891/0886-6708.27.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Intimate Partner Violence in Young Adult Couples: Nonviolent, Unilaterally Violent, and Mutually Violent Couples

Abstract: This study examined nonviolent (NV), unilaterally violent (UV), and mutually violent (MV) patterns of perpetrated intimate partner violence in relation to dyadic relationship quality and partner injury. The respondents were 1,294 young adult, Add Health partners (AHP) and their non-Add Health partners (NAHP), in dating, engaged, or in marital relationships, who were participants in Wave III of the National Longitudinal Study of Adolescent Health (Add Health). Using both partner reports of perpetration to class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 41 publications
3
19
0
3
Order By: Relevance
“…This association is less consistent in the literature partly because IPV is a complex phenomenon which may not be fully explained by a single factor or simple model [7], [23], [24]. For example, sensation seeking was associated with IPV perpetration among couples in one study [25], but not in another study conducted among male undergraduates [26]. In a third study, women with higher sensation-seeking scores reported a higher prevalence of IPV victimization whereas no significant difference of IPV victimization prevalence between high and low levels of sensation-seeking scores was observed among men [27].…”
Section: Introductionmentioning
confidence: 84%
“…This association is less consistent in the literature partly because IPV is a complex phenomenon which may not be fully explained by a single factor or simple model [7], [23], [24]. For example, sensation seeking was associated with IPV perpetration among couples in one study [25], but not in another study conducted among male undergraduates [26]. In a third study, women with higher sensation-seeking scores reported a higher prevalence of IPV victimization whereas no significant difference of IPV victimization prevalence between high and low levels of sensation-seeking scores was observed among men [27].…”
Section: Introductionmentioning
confidence: 84%
“…For example, McCarroll, Fan, and Bell (2009) and others provide rich information on couples with mutual and non-mutual violence, but when it is non-mutual, there was no information on which partner engaged in the behavior. There is a similar lack of information on all three categories in a number of other studies such as (Marcus, 2012;Swan & Snow, 2002).…”
Section: Dcts and Other Methods Of Dyadic Analysismentioning
confidence: 99%
“…In recent years, researchers examining violence have begun to focus on the overlap between victimization and perpetration of ADV (25,(30)(31)(32). The reported prevalence of the overlap between ADV victimization and perpetration varies across studies.…”
Section: Co-occurrence Of Adolescent Dating Violence Roles and Formsmentioning
confidence: 99%